Examining the Impact of Economic Globalization on Environmental Degradation in Saudi Arabia - Benzerrouk, Zakia Seid; Abid, Mehdi; Ghandri , Mohamed; Hamed, Noureddine; Ahmed Ali Adam , Fathi (International Journal of Energy Economics and Policy, 2026)
Environmental degradation has emerged as a pressing global challenge that requires continuous empirical assessment, motivating researchers to examine it. To this end, this study examines the asymmetric impact of globalization, economic growth and trade openness on the CO2 emissions in the presence of environmental Kuznets curve (EKC) in Saudi Arabia for the 1970 -2022 period. In order to investigate the effect of positive and negative shocks on the independent variable on the dependent variable, a nonlinear autoregressive distributive lag (ARDL) is used. The findings confirm that the effects of globalization and trade openness are significant and nonlinear. However, the effect of negative shocks of globalization and trade openness is more dominant on the CO2 emissions in in Saudi Arabia than the positive shocks of both variables. Moreover, the present study tests the presence of the Environmental Kuznets Curve (EKC) hypothesis in Saudi Arabia, and the findings confirm the presence of an inverted U-shape curve in the Saudi Arabia economy. Policymakers should reinforce environmental regulations, broaden green financing initiatives, and adopt international best practices to ensure that globalization supports environmental goals in the long-term.